Role of polydimethylsiloxane in properties of ternary materials based on polyimides containing zeolite Y - KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
Mixed matrix materials, containing poly(dimethylsiloxane), phosphine oxide-based polyimide, and zeolite Y were prepared by means of blending hybridisation. The thermal stability of the materials and the hydrophobic properties were enhanced. The decrease in the glass transition temperature of the materials with the increase in poly(dimethylsiloxane) content supported the polymer-chain flexibility. The pristine polyimide and the zeolite-filled polyimide exhibited the highest transparency. Fourier transform infrared (FTIR) spectroscopy confirmed that the increase in the amount of the lowest molecular mass poly(dimethylsiloxane) ingredient indicated strong alkyl and Si-O-Si stretching modes, whilst the alkyl and Si-O-Si stretching intensity decreased in the presence of the highest amount of and the highest molecular mass poly(dimethylsiloxane). The hydrophobic poly(dimethylsiloxane) moiety created an inverse relationship between the porosity of the materials (surface roughness) and the hydrophilicity. The nanocrystallite domain, identified by X-ray diffraction analysis (XRD) and possessing an exotherm crystallisation peak, occurred in the lowest amount of poly(dimethylsiloxane) with the highest molecular mass-based hybrid material. The nanocrystallite enhanced the storage modulus as determined by the dynamic mechanical analyser (DMA). The nanocrystalline formation resulted in a slight increase in the alkyl stretching and the Si-O-Si stretching of the lowest amount of and the highest molecular mass poly(dimethylsiloxane)-containing material over those of the lowest molecular mass poly(dimethylsiloxane) in the same amounts of material involved. (C) 2016 Institute of Chemistry, Slovak Academy of Sciences
Keywords: phosphors; porous materials; polymeric composites; morphology; nanocrystalline; MEMBRANES; BLOCK